High relatedness of bioinformatic data and realistic experimental works on the potentials of Fasciola hepatica and F. gigantica cathepsin L1 as a diagnostic and vaccine antigen - Fereig, Ragab M.; Metwally, Samy; El-Alfy, El-Sayed; Abdelbaky, Hanan H.; Shanab, Obeid; Omar, Mosaab A.; Alsayeqh, Abdullah F. (Frontiers in Public Health, 2022)
Introduction Fascioliasis is a parasitic foodborne disease caused by the liver flukes, Fasciola hepatica and F. gigantica. Such parasites cause serious illness in numerous domestic animals and also in humans. Following infection, the parasite secretes a variety of molecules that immediately interact with the host immunity to establish successful infection. These molecules include cathepsin L peptidase 1 (CatL1); the highly investigated diagnostic and vaccine antigens using various animal models. However, a few studies have analyzed the potentials of FhCatL1 as a diagnostic or vaccine antigen using bioinformatic tools and much less for FgCatL1. The present study provides inclusive and exclusive information on the physico-chemical, antigenic and immunogenic properties of F. hepatica cathepsin L1 (FhCatL1) protein using multiple bioinformatic analysis tools and several online web servers. Also, the validation of our employed available online servers was conducted against a huge collection of previously published studies focusing on the properties of FhCatL1as a diagnostic and vaccine antigen. Methods For this purpose, the secondary, tertiary, and quaternary structure of FhCatL1 protein were also predicted and analyzed using the SWISS-MODEL server. Validation of the modeled structures was performed by Ramachandran plots. The antigenic epitopes of the protein were predicted by IEDB server. Results and discussion Our findings revealed the low similarity of FhCatL1 with mammalian CatL1, lacking signal peptides or transmembrane domain, and the presence of 33 phosphorylation sites. Also, the containment of FhCatL1 for many topological, physico-chemical, immunological properties that favored its function of solubility and interaction with the immune components were reported. In addition, the earlier worldwide reports documented the high efficacy of FhCatL1 as a diagnostic and vaccine antigen in different animals. Altogether, FhCatL1 is considered an excellent candidate for using in commercialized diagnostic assays or vaccine products against fascioliasis in different animal species. Our assessment also included FgCatL1 and reported very similar findings and outputs to those of FhCatL1.